“CULTURAL MURAL” SEBAGAI VISUALISASI ESTETIKA KONTEMPORER PADA LAPANGAN ASTAGINA, DENPASAR. - Ni Nyoman Sri Rahayu; Luh Gde Niti Swari (LPPM Institut Desain dan Bisnis Bali, 2020)
ABSTRACT Community Service Activities were also organized by IDB Bali (Bali Design and Business Institute), in the form of mural design activities located in Astagina Court, Padangsambian Klod Village, Denpasar City. In this community service, a mural with a cultural and aesthetic function was created. The cultural function is manifested by presenting the unique and distinctive culture of Denpasar City, some of which are Legong dance, Baris Dance, Genggong traditional music, Janggan kites, traditional children's games, and etcetera. This mural is not just an art medium without a message, but its also able to bring out the identity of Denpasar City. The aesthetic function is displayed in a contemporary design that were displayed as a contemporary impression so that it can encourage and increase comfort for Astagina Court’s users. The implementation method used in the activities includes sketching the initial image first. This sketches aims to make it easier for students to get an initial picture before creating the mural on the wall. This mural design has the theme of a typical Denpasar culture. In the site of the implementation, students and lecturers began cleaning the wall area and amplifying the walls. Followed by basic paint on the wall, and made sketches on the wall. Then the next day continued with coloring and finishing using Dulux paint. This activity was carried out by IDB Bali students who are members of an art club called “Perkamen”, involving 40 students and 45 lecturers from IDB Bali (Bali Design and Business Institute) and New Media College.